Work Discipline and Work Motivation’s Impact on Teacher’s Performance - Febriani, Nani; Ahyani, Nur; Fitriani, Yessi (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to analyze, identify, and describe the impact of work discipline and work motivation on the performance of public elementary school teachers in Cluster 1, Rambutan District, as well as to simultaneously analyze, identify, and describe the impact of both factors on those teachers’ performance. This study used a quantitative methodology. This approach allows researchers to quantify the impact of work motivation and work discipline on the effectiveness of public elementary school teachers in Cluster 1’s Rambutan District. The study’s findings indicate that work discipline has a favorable and significant impact on the effectiveness of public elementary school teachers in Cluster 1’s Rambutan District. In terms of population and sample, 114 people were included in the study population, while 94 people made up the actual research sample. The trial sample, which might include up to 20 persons, is meant to be a sample for evaluating research tools to establish the reliability of the assembled tool. Questionnaires and documentation are the methods used to gather research data. The work discipline variable’s influence contribution is categorized under “low influence.” In Cluster 1, Rambutan District, there is a positive and significant relationship between job motivation and the effectiveness of public elementary school instructors. The work motivation variable’s influence contribution falls within the “fairly high influence” group. Workplace motivation and discipline both have a positive and significant impact on the effectiveness of public elementary school teachers in Cluster 1, Rambutan District.